236. The Impact of Earlier Intervention by an Antimicrobial Stewardship Team on Appropriate Antimicrobial Therapy for Specific Antimicrobial Agents. (26th November 2018) - Hagiwara, Daiki; Sato, Keisuke; Kamada, Mitsuhiro; Moriwaki, Norihiro; Nakano, Takafumi; Shiotsuka, Shouichi; Kamimura, Hidetoshi; Togawa, Atsushi; Takamatsu, Yasushi; Takata, Tohru
Abstract: Background: The optimal timing of intervention to obtain significant effects with regard to reducing the consumption of antimicrobial agents or antimicrobial-resistant bacteria in facilities that lack the manpower to maintain an antimicrobial stewardship team (AST) is not well-known. Methods: An observational retrospective study was performed at Fukuoka University Hospital between April 1, 2013 and March 31, 2016 to evaluate the optimal timing of intervention on appropriate antimicrobial therapy for specific antimicrobial agents, including broad-spectrum antimicrobial agents (piperacillin–tazobactam, carbapenems, fluoroquinolones) and anti-MRSA (vancomycin, teicoplanin, daptomycin, and linezolid) agents. In period 1, interventions were performed for patients using specific antimicrobial agents for >14 days. In period 2, interventions were performed for patients using anti-MRSA agents, and in period 3, interventions were performed for patients using any specific antimicrobial agents, regardless of the days of use, on a weekly basis. The effects on antimicrobial use, the antimicrobial-resistant bacteria, and the clinical outcomes among the three periods were compared. Results: The AUDs of piperacillin–tazobactam and carbapenems decreased significantly (10.8 → 9.2 and 15.7 → 14.2; period 2 vs. period 3, P < 0.05). The rates of piperacillin–tazobactam, meropenem and levofloxacin resistance in Pseudomonas aeruginosa isolates decreased from 13.8%, 16.2%, 11.9% in period 1 to 10.4%, 8.7%, 6.5% in period 3, respectively. The annual costs of these antimicrobials decreased according to the period: period 1, US$ 1, 080, 000; period 2, US$ 944, 000; and period 3, US$ 763, 000 (period 3 vs. period 1, P <0.01). No recurrence was observed within 7 days after intervention and the mortality rate and length of stay did not change to a statistically significant extent in any of the study periods. Conclusion: When interventions were performed once a week by an ASP team, accelerating the timing of intervention from patients with >14 days of use to all patients treated with the specific antimicrobial agents was significantly more effective for reducing the consumption of antimicrobials leading to reduction of the related costs and antimicrobial-resistant P. aeruginosa without compromising the patient outcomes. Disclosures: T. Takata, Taisho Toyama Pharmaceutical Co. Ltd.: Speaker's Bureau, Speaker honorarium